Utilizing Candlenut Fruit as an Eyebrow Thicken Solution - Agus Syam; Mohamad Ikbal Riski A. Danial; Muhammad Jufri; Fitrah Widyawati; Rahmi Rahmi (PT. Global Research Collaboration, 2025)
Candlenut fruit (Aleurites molucana) has long been known as a natural ingredient that is full of benefits, both in beauty care. In today's modern era, when people are increasingly aware of the importance of natural and environmentally friendly ingredients, candlenut fruit is again in the spotlight as a traditional solution that is proven to be effective and has high economic value. One of the most popular benefits of candlenut fruit is its ability to thicken and nourish eyebrows naturally. The oil produced from candlenut fruit contains essential fatty acids and vitamin E, which are very good for stimulating hair growth, strengthening roots, and nourishing hair follicles. Regular use of candlenut oil on eyebrows has been shown to accelerate new hair growth, making eyebrows look thicker, blacker, and healthier, without the need for using harmful chemicals. With product innovation and the right marketing strategy, candlenut fruit products are not only able to meet the needs of the domestic market, but also have the opportunity to penetrate the export market. Therefore, optimal utilization of candlenut fruit provides dual benefits as a natural solution in beauty care, as well as a means of economic empowerment through creative and sustainable efforts. Candlenut fruit is known to have interesting benefits for beauty, especially in thickening eyebrows naturally. The oil produced from candlenut contains nutrients that can stimulate hair growth in the eyebrow area, making it look thicker and healthier. The use of candlenut oil is quite simple, usually by applying it regularly to the eyebrows before going to bed. These natural properties make candlenut a choice ingredient in various traditional care products, especially for eyebrow care. Its abundant availability in Indonesia also makes candlenut an easily available and economical beauty solution.